Pleomorphic dermal sarcoma. UK multidisciplinary team members have wide variation in opinions on management and pathways - Carrie Newlands; Elizabeth Gruber; Franel Le Grange; Rajiv Anand; Simon Whitley; Stephen Keohane (Clinical Surgical Oncology)
Background: Pleomorphic Dermal Sarcoma (PDS) is increasing in incidence and evidence-based guidelines as to optimal management are lacking. It is unclear from guidance which cancer MDTs should be involved in the care of patients with PDS and there is anecdotally widespread variation in patient pathways and management. Objective: To determine current pathways and opinions regarding management of PDS amongst members of relevant UK MDTs. Methods: A survey was devised, piloted, and circulated to MDT members, via national organisations. Responses were analysed using online SurveyMonkey tools. Results: 105 consultant members of a relevant MDT responded, including 19 skin and 2 sarcoma MDT Chairs. There was widespread variation in referral pathways, with 25.7% of participants reporting no sarcoma MDT involvement in a hypothetical case of a patient with a 2.1 ​cm primary PDS of the scalp, with no clinically apparent regional or distant metastases (N0M0). Opinions on the correct peripheral and deep surgical excision margins (PM/DM) varied, with the majority choosing a 10 ​mm PM (53.3%). Taking periosteum as the deep margin was preferred by 50.5%. Histological clearance margins of at least 5 ​mm at the PM and at least 1 ​mm at the DM were preferred by 33.3% of participants and deemed to be acceptable as definitive treatment. Imaging at diagnosis and for surveillance showed wide variation, with 24.8% not offering any imaging at diagnosis, in the above case. Conclusions: PDS pathways and clinical management have been shown to vary widely amongst UK MDT members. A modified Delphi study is proposed to develop consensus-based guidance.